EXAMINING THE ROLE OF ZAKAT AS ISLAMIC SOCIAL FINANCE AND ITS CONTRIBUTION TO MULTIDIMENSIONAL POVERTY ALLEVIATION - Qanita, Ariza (Program Studi Manajemen Zakat dan Wakaf, 2024)
Poverty is often only interpreted as an economic problem. Even though poverty is a multidimensional problem. Zakat as an Islamic Social Finance instrument which has an important role in reducing poverty must also target these dimensions. This research aims to analyze the role of zakat in reducing poverty from a material, social and spiritual perspective. The method used in this research is qualitative with literature review. The data used in this research is secondary data in the form of scientific articles and other publications that are appropriate to the research topic. The research results show that zakat has a role in reducing material poverty, social poverty and spiritual poverty. Zakat can alleviate material poverty by increasing the income of mustahik. Zakat can alleviate social poverty through strengthening solidarity and Islamic brotherhood in society which can become social capital for mustahik. Zakat can also increase the religiosity of mustahik through strengthening Islamic values as an effort to reduce spiritual poverty.